Melanistic White-fronted and other Grey Geese - Harrison, Jeffery; Hudson, Michael (Wildfowl, 1967)
It seems that all the adult grey geese mentioned have a tendency to produce a melanistic pattern, which reaches its normal extreme in the Greenland White-fronted Goose... It seems highly unlikely that any external factor could be found to explain the development of this melanistic pattern. The controlling mechanism is almost certainly genetic. This suggests that the grey geese of the genus Anser were preceded in the evolutionary tree by the black geese of the genus Branta.